Leadership Style of Head Nurses against Job Satisfaction and Organizational Commitment of Staff Nurses - Lili Amaliah; Iluminada Fajardo Castigador; Benjamin Yngente; Maria Linda Buhat; Theofile Salcedo; Eufemia F Octaviano; Allan Yngente (Media Kesehatan Masyarakat Indonesia, 2021)
The leadership and motivation styleis an essential factor in supporting the performance of nurses. The study was undertaken to determine the correlation between the leadership style to the job satisfaction, and organizational commitment among the head nurses and staff nurses from the government and private hospitals in Serang, Banten, Indonesia. The study used descriptive corelational design. The samples were limited, involving 289 respondents from dr. Drajat Prawiranegara Hospital, Serang (18 head nurses and 183 staff nurses) and Sari Asih Hospital, Serang (6 head nurses and 82 staff nurses). The study found a low positive relationship of the head nurses' transformational leadership style and transactional leadership style against the staff nurses' job satisfaction, r-coefficients of 0.370 and 0.485, respectively. Also, a moderate positive correlation was found on transformational leadership style and transactional leadership style of the head nurses against the organizational commitment of the staff nurses, rcoefficient of 0.606 and 0.609, respectively. It suggested that the staff nurses should be more responsive to the duty inseparable from the rights and obligations as an employee while the head nurse needs to pay attention to physical readiness, mental and psychological of subordinates.